Pelanggaran Etika Terkait Pemalsuan Dokumen oleh Advokat - Sihotang, Josua Ferdinand; Sihombing, Albert Hasea Samuel; Simamora, Tesalonika Amazia; Az-Zahra, Fatimah; Wulandari, Hania; Yesica, Shely; Steffanie, Josephine; M, Mulyadi (Media Hukum Indonesia (MHI), 2025)
The legal profession of advocacy plays a crucial role within Indonesia’s legal system as a guardian of justice and protector of human rights. However, ethical violations, particularly document forgery, pose significant challenges that threaten the integrity of the profession. This study aims to analyze the regulation of the Advocate’s code of ethics concerning document forgery, the applicable sanctions, and the impact on the judicial system and public trust. Using a normative juridical approach, this research examines provisions from the Advocate Law, the Indonesian Advocate Code of Ethics (KEAI), and the Indonesian Criminal Code (KUHP). The findings reveal that advocates involved in document forgery may face criminal, ethical, and administrative sanctions. Such violations not only harm clients but also establish a negative precedent for the rule of law. Therefore, stricter oversight, consistent enforcement of sanctions, and the enhancement of ethical awareness among advocates are essential to maintain the profession’s integrity. Preventing and addressing ethical violations are critical steps in preserving public confidence in Indonesia’s legal system.